2018
DOI: 10.1002/aur.1946
|View full text |Cite
|
Sign up to set email alerts
|

Click‐evoked auditory brainstem responses and autism spectrum disorder: A meta‐analytic review

Abstract: Auditory brainstem responses (ABR) may be associated with ASD, but participant characteristics and assessment protocols vary considerably across individual studies. Our goal is to combine the results across these studies to facilitate clarity on the topic. Doing so represents a first step in evaluating whether ABRs yield potential for informing the etiology of ASD risk and/or ASD symptom profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…The ABR has provided the most insight into the function of brainstem centers in ASD. The majority of studies of the ABR in subjects with ASD over the past 40 years provide evidence that subjects with ASD have smaller amplitudes in waves I, II, III, IV, and V (Ornitz et al, 1972 ; Gillberg et al, 1983 ; Martineau et al, 1987 , 1992 ; Klin, 1993 ), longer latencies between waves I-III and waves I-V (Taylor et al, 1982 ), and longer latencies/slower responses (Ornitz, 1969 ; Student and Sohmer, 1978 ; Rosenblum et al, 1980 ; Sohmer, 1982 ; Tanguay et al, 1982 ; Gillberg et al, 1983 ; Sersen et al, 1990 ; Thivierge et al, 1990 ; Wong and Wong, 1991 ; Maziade et al, 2000 ; Kwon et al, 2007 ; Roth et al, 2012 ; Azouz et al, 2014 ; Taş et al, 2017 ; Miron et al, 2018 , 2021 ; Ramezani et al, 2019 ; Delgado et al, 2021 ; reviewed in Talge et al, 2018 ). These longer latency and lower amplitude responses have been attributed to the immaturity of brainstem circuits (Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ABR has provided the most insight into the function of brainstem centers in ASD. The majority of studies of the ABR in subjects with ASD over the past 40 years provide evidence that subjects with ASD have smaller amplitudes in waves I, II, III, IV, and V (Ornitz et al, 1972 ; Gillberg et al, 1983 ; Martineau et al, 1987 , 1992 ; Klin, 1993 ), longer latencies between waves I-III and waves I-V (Taylor et al, 1982 ), and longer latencies/slower responses (Ornitz, 1969 ; Student and Sohmer, 1978 ; Rosenblum et al, 1980 ; Sohmer, 1982 ; Tanguay et al, 1982 ; Gillberg et al, 1983 ; Sersen et al, 1990 ; Thivierge et al, 1990 ; Wong and Wong, 1991 ; Maziade et al, 2000 ; Kwon et al, 2007 ; Roth et al, 2012 ; Azouz et al, 2014 ; Taş et al, 2017 ; Miron et al, 2018 , 2021 ; Ramezani et al, 2019 ; Delgado et al, 2021 ; reviewed in Talge et al, 2018 ). These longer latency and lower amplitude responses have been attributed to the immaturity of brainstem circuits (Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported abnormal auditory processing in ASD and/or other disorders such as schizophrenia, measured by magnetoencephalography (MEG), electroencephalography (EEG), and auditory brainstem responses (ABR). Previous electrophysiology studies have also observed prolonged latencies of other components in clinical populations compared to neurotypically developing controls, with delayed auditory responses observed at mid-brainstem levels as well as primary/secondary auditory cortex [Oram Cardy et al, 2005, Roberts et al, 2012, Rojas., 2014, Kikuchi et al, 2015, Damaso et al, 2015, Berman et al, 2016, Schwartz et al, 2018, Talge et al, 2018, Matsuzaki et al, 2019]. The ability to detect an auditory change (e.g., pitch, frequency, syllable) is an important feature of the auditory system, with impaired change detection likely contributing to downstream language and communication impairment [Schwartz et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated auditory processing differences in ASD in terms of both response amplitude and timing that are seen from the earliest brainstem responses [e.g., Talge, Tudor, & Kileny, ] to late cortical responses [see Bomba & Pang, ; Jeste & Nelson, ; O'connor, for reviews]. Tharpe et al [] showed that, despite normal auditory thresholds, brain stem responses were more variable in ASD.…”
Section: Introductionmentioning
confidence: 99%